Analisis Deiksis Eksofora dalam Novel “Bulan Patah” Karya Maria Matildis Banda - Caesilia Syrilla; Marselus Robot; Margareta P.E. Djokaho (YASIN, 2026)
Pragmatic studies, particularly exophoric deixis, are important for understanding the meanings of utterances that refer to contexts outside the text in literary works. The novel Bulan Patah by Maria Matildis Banda contains various forms of exophoric deixis that contribute to constructing meaning and clarifying the relationships among characters, time, place, and social situations in the story. This study aims to describe the use of exophoric deixis in the novel Bulan Patah by Maria Matildis Banda. The study employed a qualitative descriptive method with a pragmatic approach based on Bambang Kaswanti Purwo’s theory of deixis. The data source was the novel Bulan Patah, while the data consisted of words, sentences, and paragraphs containing exophoric deixis. The data were collected through a literature review and coding cards and were then analyzed by identifying and classifying the forms of deixis based on the context of the utterances. The results showed that exophoric deixis in the novel included person, place, time, and social deixis. A total of 929 instances of person deixis, 57 instances of place deixis, 106 instances of time deixis, and 652 instances of social deixis were identified. The use of these forms of deixis functions as a referential marker whose interpretation depends on the context of the speech situation, including the speaker, interlocutor, time, place, and social relationships. These findings confirm that exophoric deixis helps readers understand the meanings of utterances more accurately while clarifying the relationships among characters, spatial and temporal settings, and social situations in the novel. This study contributes to the development of pragmatic studies and can be used as a research reference and teaching material in Indonesian language and literature education.